AKTIVITAS ANTIINFLAMASI SENYAWA AKTIF DAUN JAWER KOTOK (Plectranthus scutellarioides (L.)R.Br.) MELALUI INHIBISI Siklooksigenase-2 SECARA IN SILICO - Maharani, Alya Rizqi; Purwono, Rini Madyastuti; Siswandi, Riki; Nurkarimah, Dona Astari; Farhamzah (Jurnal Buana Farma, 2025)
Inflammation is the body’s response to harmful stimuli, and it plays a crucial role in boosting immunity. However, if inflammation is not managed properly, it can lead to degenerative diseases. This research aims to analyze the potential of Plectranthus scutellarioides (L.) R. Br. leaves as an anti-inflammatory agent. The study employs an in silico molecular docking method, using the active compound from the plant as the test ligand and the COX-2 receptor as the target. The results indicate that the test ligand, Antosianin, shows the best interaction as an inhibitor of the target receptor, as demonstrated by its superior affinity energy value compared to the other test ligands.